Acute kidney injury after pediatric cardiac surgery - Shi-Min Yuan (Elsevier, 2019)
Acute kidney injury (AKI) is a common complication of pediatric cardiac surgery and is associated with increased morbidity and mortality. Literature of AKI after pediatric cardiac surgery is comprehensively reviewed in terms of incidence, risk factors, biomarkers, treatment and prognosis. The novel RIFLE (pediatric RIFLE for pediatrics), Acute Kidney Injury Network (AKIN) and Kidney Disease Improving Global Outcomes (KDIGO) criteria have brought about unified diagnostic standards and comparable results for AKI after cardiac surgery. Numerous risk factors, either renal or extrarenal, can be responsible for the development of AKI after cardiac surgery, with low cardiac output syndrome being the most pronounced predictor. Early fluid overload is also crucial for the occurrence of AKI and prognosis in pediatric patients. Three sensitive biomarkers, neutrophil gelatinase-associated lipocalin, cystatin C (CysC) and liver fatty acid-binding protein, are regarded as the earliest (increase at 2-4 h), and another two, kidney injury molecule-1 and interleukin-18 represent the intermediate respondents (increase at 6-12 h after surgery). To ameliorate the cardiopulmonary bypass techniques, improve renal perfusion and eradicate the causative risk factors are imperative for the prevention of AKI in pediatric patients. The early and intermediate biomarkers are helpful for an early judgment of occurrence of postoperative AKI. Improved survival has been achieved by prevention, renal support and modifications of hemofiltration techniques. Further development is anticipated in small children. Key Words: acute kidney injury, cardiac surgical procedures, pediatrics